Evaluating antimicrobial activities of Acanthus ilicifolius L. and Heliotropium curassavicum L against bacterial pathogens: an in-vitro study - Chinnathambi Pothiraj; Paulraj Balaji; Ramkumar Shanthi; Muthukrishnan Gobinath; Rangasamy Suresh Babu; Abdullah Al-Dosary Munirah; Atef Hatamleh Ashraf; Kamatchi Ramesh Kumar; Veeramani Veeramanikandan; Ramasubramanian Arumugam (Elsevier, 2021)
Background: Biomedical research, recently, focus more on searching for biomasses that contain extractable biologically active components for formulating new drugs. Halophytes growing in hyper saline conditions are expected to produce stress alleviating bioactive compounds. These phytochemicals could be the better raw materials for formulating new drugs. Methods: The purpose of this work was to describe physiologically active compounds from Acanthus ilicifolius and Heliotropium curassavicum that had antimicrobial, antioxidant and nutraceutical properties utilizing a variety of solvents. Analysis of bioactive compounds included the application of common phytochemical screening assays, proximate analysis, FTIR analysis and antioxidant assays. The disc diffusion technique was used to determine the antibacterial activity of the plant extracts. Results: Highest extraction yield was observed with methanol. A. ilicifolius methanolic extracts included a variety of bioactive components, including alkaloids, saponins, phenolics, flavonoids, steroids, cardiac glycosides, tannins, and terpenoids. H. curassavicum extracts showed the presence of all the phytochemicals except cardiac glycosides. The overall phenolic concentration and antioxidant capacity of A. ilicifolius were substantially greater. The antimicrobial assays explored that among the tested bacterial pathogens viz., Bacillus subtilis, Escherichia coli, Klebsiella pneumoniae, Staphylococcus aureus, Streptococcus pneumoniae, significant level of control was observed in E. coli, K. pneumoniae and B. subtilis, which were significantly susceptible to both the plant extracts at a concentration of 50 μg/ml. Conclusion: The reports from the current investigation explored the possibility of utilizing these halophytes in nutraceutical formulations. The current study sheds light on the possibility of halophytes as natural secondary metabolites and bioactive chemicals with potential for antimicrobials.